(untitled) (International Journal of Engineering and Computer Science, 2017)
As we see around the whole world is getting converted into automation and people are living their lives more comfortably and easily as many advanced technology appliances are available in the market. As the technology expands more energy is required to operate the appliances. So the energy conservation is the main need nowadays. So the appliances should be switched off when there is no need to conserve more energy. The machines which are at remote places need to be control and monitor from any other place. In the large industries machines are located globally anywhere and every time that person cannot go there to operate and monitor the machines. So this projects builds such a system which can control and monitor functioning of the machines globally with the help of internet i.e internet of things. Here Raspberry PI acts as main controller which obtains input from user through internet and takes appropriate action. Raspberry PI controller will be connected to the appliances and machines with the help of relays. Weaved cloud services enables a secure internet connection and a billions of user can connect to the internet and can access the remote place machines. Here weaved cloud service binds public IP address of raspberry PI with fix IP address provided by server.